A treatise on woonen trestle bridges and their concrete substitutes according to the present practice on American railroads - Foster, Wolcott C. (Chapman & Hall, 1913)
Wooden trestle bridges were still very much to the fore on branch lines in the early 20th century, and this treatise also covers their concrete substitutes.